Acquiring a suited Information Resource Manager (IRM) as a prelim to having a CRM (using relevance trees) - Rafols, Bernard J. (University of the Philippines Diliman, Technology Management Center, 2009)
As the IT service arm of McDonald's Philippines, Creative Gateway Inc. has committed to deliver the needed IT support services to its restaurants nationwide that should be available anytime and anywhere needed, whether through remote or on-site. Once done with a business process re-engineering (BPR), CGI's long term plan is to acquire a CRM to complement in having positive customer relations. However, acquiring an Information Resource Manager (IRM) could be a prelude to the expensive CRM. Using Relevance Tree, we can determine the most appropriate path by arranging, in a hierarchical order, the objectives, sub-objectives and tasks in order to ensure that all possible ways of achieving the objectives can be found.